You are here:

- Home
- Science
- Math for Kids
- Algebra
- Algebra Question

Advertisement

6.5-2

If f(x)=x^2-4 and g(x)=-3x^2, find

f(x(x))

(yes, that's how it is written)

Thanks, much appreciated!

It seems to me that there is a typo in the problem.

f(x(x)) does not make sense, unless the "x(x)" means x*x=x^2, but then

why would they give g(x)?

If it is f(x^2), then it would be f(x^2)=(x^2)^2-4=x^4-4

If it is supposed to be f(g(x)), as I suspect, then it would be

f(g(x))=f(-3x^2)=(-3x^2)^2-4=9x^4-4

- Add to this Answer
- Ask a Question

Rating(1-10) | Knowledgeability = 10 | Clarity of Response = 10 | Politeness = 10 |

Comment | Wow, you answered my question even with a typo. Really great work! |

Algebra

Answers by Expert:

Hello, I am a college professor of mathematics and regularly teach all levels from elementary mathematics through differential equations, and would be happy to assist anyone with such questions!

Over 15 years teaching at the college level.**Organizations**

NCTM, NYSMATYC, AMATYC, MAA, NYSUT, AFT.**Education/Credentials**

B.S. in Mathematics from Rensselaer Polytechnic Institute

M.S. (and A.B.D.) in Applied Mathematics from SUNY @ Stony Brook